A Clinical and Laboratory Profile of Sthaulya W.S.R to Obesity and its Management by Amritadya Guggulu - Triveni Raina,; Dalip Sharma, (International Journal of Ayurveda and Pharma Research, 2022)
In Ayurveda, it is regarded as Medoroga which includes fat tissue and fat metabolism, results from the excessive accumulation of Meda (fat/ adipose tissue) and Mamsa (flesh/ muscle tissue) leading to flabbiness of hips, abdomen, and breast. It is considered as Santarpanottha Vikara and counted one among the Ashtnindita Purusha by Ayurvedic Acharayas. According to Ayurveda, Sthoulya begins with an imbalance of Doshas (Vata, Pitta and Kapha), Agni (digestive fire), Malas (waste products) or an imbalance of Srotas (microcirculatory channels). This collection of imbalances then interferes with the formation of tissues or Dhatus and leads to a tissue imbalance that we experience as Sthoulya. It is most prevailing condition being faced by majority of the population, but yet among the most neglected health problem in the world. In this regard approach of this study is to give safer, comprehensive and rational option for treating Sthaulya (Obesity) and this is a humble attempt to probe into the different pathophysiological aspects behind Sthaulya, taking into consideration the classical therapy coupled with modern interpretations. Amritadya Guggulu by the virtue of its Rasapanchaka (Rasa- Katu, Tikta, Kashaya, Guna- Laghu, Ruksha and Virya- Ushna, Vipaka- Katu, Dosha Karma- Kapha Vatashamaka) is effective in the management of Sthoulya including all Kapha predominant pathologies, leading to Samprapti Vigatana of Sthoulya. Hence this study is carried out to establish the efficacy of the treatment considering the clinical and laboratory profile of obesity (Sthoulya). The study was done on 30 patients taken from both IPD & OPD of RGGPG Ayurvedic College and Hospital, Paprola, H.P. The duration of the trial was 60 days with follow up of 15 days and the observations obtained are analyzed statistically after the end of the study.